STATE OF HEALTH IN CHILDREN OF PRESCHOOL AGE FROM POOR FAMILIES - T.V. Yakovleva; E.A. Kurmaeva; S.Ya. Volgina ("Paediatrician" Publishers LLC, 2008)
Poverty is the actual problem in modern Russia. Complex clinical, laboratory and instrumental diagnostics and social and hygienic research in 108 children at the age of 5-7 years from poor families (basic group) was performed. 108 children from families with mean income, comparable to the children from basic group by age and sex, formed control group. The peculiarities of state of health in children were discovered using appeal ability and advanced examination and physical growth and development data, school readiness was estimated. Authors made a conclusion of health group. Key words: children of preschool age, poverty, state of health.